2018
DOI: 10.3389/fneur.2018.00425
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Environmental Enrichment on Glutathione-Mediated Xenobiotic Metabolism and Antioxidation in Normal Adult Mice

Abstract: Olfactory bulb (OB) plays an important role in protecting against harmful substances via the secretion of antioxidant and detoxifying enzymes. Environmental enrichment (EE) is a common rehabilitation method and known to have beneficial effects in the central nervous system. However, the effects of EE in the OB still remain unclear. At 6 weeks of age, CD-1® (ICR) mice were assigned to standard cages or EE cages. After 2 months, we performed proteomic analysis. Forty-four up-regulated proteins were identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…Other previous studies suggested that EE inhibits apoptosis, enhances neuroprotection in the brain of rodent PD models [ 39 , 46 ], and improves neurobehavioral functions in brain disorders including PD [ 13 , 47 ]. It has been suggested that EE can also be the key to provide for the stimulation of various brain regions [ 13 , 48 , 49 , 50 ]. Therefore, the inhibition of apoptosis through protecting cell proliferation of neurogenesis area is a promising therapeutic strategy in the various brain regions of PD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other previous studies suggested that EE inhibits apoptosis, enhances neuroprotection in the brain of rodent PD models [ 39 , 46 ], and improves neurobehavioral functions in brain disorders including PD [ 13 , 47 ]. It has been suggested that EE can also be the key to provide for the stimulation of various brain regions [ 13 , 48 , 49 , 50 ]. Therefore, the inhibition of apoptosis through protecting cell proliferation of neurogenesis area is a promising therapeutic strategy in the various brain regions of PD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous pieces of evidence have demonstrated that precursor cell proliferation was impaired by the onset of PD [41], and that apoptosis was induced by exposure to toxic compounds in PD [42][43][44][45]. Other previous studies suggested that EE inhibits apoptosis, enhances neuroprotection in the brain of rodent PD models [39,46], and improves neurobehavioral functions in brain disorders including PD [13,47]. It has been suggested that EE can also be the key to provide for the stimulation of various brain regions [13,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glutathione activity is an important process involved in removing reactive oxygen species (ROS) generated endogenously during xenobiotic metabolism [40]. Glutathione redox is the marker for oxidative stress that plays a crucial role in resisting oxidative stress and maintaining cellular oxidationreduction homeostasis [41].…”
Section: Qrt-pcr Indicates Alteration Of Oxidative Stress-related Genes In Exposure To Agnpsmentioning
confidence: 99%